Conditions for the maximal dissipativity of almost bounded perturbations of smooth restrictions of operators adjoint to symmetric ones - Storozh, O. G.; Shuvar, O. B. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We establish conditions for the maximal dissipativity of one class of densely-defined closed linear operators in a Hilbert space. The results obtained are applied to the investigation of some special differential boundary operators.